A novel crosslinking method for improved tear resistance and biocompatibility of tissue based biomaterials. (October 2015) - Tam, Hobey; Zhang, Will; Feaver, Kristen R.; Parchment, Nathaniel; Sacks, Michael S.; Vyavahare, Naren
Abstract: Over 300, 000 heart valve replacements are performed annually to replace stenotic and regurgitant heart valves. Bioprosthetic heart valves (BHVs), derived from glutaraldehyde crosslinked (GLUT) porcine aortic valve leaflets or bovine pericardium are often used. However, valve failure can occur within 12–15 years due to calcification and/or progressive degeneration. In this study, we have developed a novel fabrication method that utilizes carbodiimide, neomycin trisulfate, and pentagalloyl glucose crosslinking chemistry (TRI) to better stabilize the extracellular matrix of porcine aortic valve leaflets. We demonstrate that TRI treated leaflets show similar biomechanics to GLUT crosslinked leaflets. TRI treated leaflets had better resistance to enzymatic degradation in vitro and demonstrated better tearing toughness after challenged with enzymatic degradation. When implanted subcutaneously in rats for up to 90 days, GLUT control leaflets calcified heavily while TRI treated leaflets resisted calcification, retained more ECM components, and showed better biocompatibility.